Polyethylene glycol‐based ultrasonic‐assisted enzymatic extraction, characterization, and antioxidant activity in vitro and in vivo of polysaccharides from Lonicerae japonica leaves. Issue 11 (13th September 2019) - Wu, Wei; Huang, Tingrong; Xiang, Fu
Abstract: In this paper, polyethylene glycol (PEG)‐based ultrasonic‐assisted enzymatic extraction (UAEE) was employed in polysaccharides extraction from Lonicerae japonica leaves (LJLP). The optimal extraction conditions (extraction time of 33 min, PEG concentration of 30%, and ultrasonic power of 191 W) were obtained by Box–Behnken design (BBD). Under this condition, the LJLP yield was 14.76%. Furthermore, LJLP was identified as a typical heteropolysaccharide considering the main constitutive monosaccharides include galactose (32.3%), glucose (20.9%), and ribose (15.2%). Moreover, LJLP exhibited high total reducing power and considerable scavenging activities on superoxide radicals, in a concentration‐dependent manner in vitro. In addition, antioxidant analysis in vivo revealed that for the LJLP‐treated mice, the superoxide dismutase (SOD), glutathione peroxidase (GSH‐Px), catalase (CAT) activities, and total antioxidant capacity (TAOC) were significantly increased, while the level of malondialdehyde (MDA) was decreased in both serum and liver. Abstract : Lonicera japonica is one of the most important natural sources of chlorogenic acid and other active compounds, which is focused on flower buds. Lonicera japonica leaves could be used as the cheapest raw materials for polysaccharide recovery. The recovery of these valuable components from the leaves could improve the economy for plant polysaccharides and minimize the waste of natural resources.